Peningkatan Pengetahuan dan Keterampilan Penggunaan Mendeley Bagi Mahasiswa Program Studi Pendidikan Matematika PSDKU Universitas Pattimura Kabupaten Maluku Barat Daya - Sisilia Marcelina Taihuttu; Fenty Madelin Madubun; Fernando Tantaru (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The use of technology in academics is one of the important factors in supporting learning and research activities, especially among students. This community service aims to improve the knowledge and skills of students of the PSDKU Mathematics Education Study Program, Pattimura University, Southwest Maluku Regency in using Mendeley as a reference management tool. The method used in this study is an experimental approach with a direct practice-based training model. Participants consisted of students of the PSDKU Mathematics Education Study Program, Pattimura University, Southwest Maluku Regency. The results of the study showed a significant increase in students' knowledge and skills in managing academic references using Mendeley, including in the aspects of compiling bibliographies, automatic citations, and organizing documents. These findings indicate that training in the use of scientific reference software such as Mendeley can have a positive impact on the quality of students' academic results.